Comparison of two-risk assessment algorithms for preeclampsia in first trimester with consecutive intake of low-dose aspirin in the high-risk group – an observational study. (4th March 2018) - Lakovschek, Ioana-Claudia; Csapo, Bence; Kolovetsiou-Kreiner, Vassiliki; Mayer-Pickel, Karoline; Reif, Philipp; Stern, Christina; Ulrich, Daniela; Lang, Uwe; Obermayer-Pietsch, Barbara; Cervar-Zivkovic, Mila
Abstract: We analyzed outcome of women screened for preeclampsia with two different multifactorial risk algorithms (Predictor ® Software by PerkinElmer, PerkinElmer, Waltham, MA; PERK-group: n  = 214 and Viewpoint ® by GE Healthcare, Dornstadt, Germany; VIEW-group: n  = 209) in first trimester. Women at high risk for developing preeclampsia were advised to take low-dose acetylsalicylic acid (LDA). Screening positive rates for early onset preeclampsia differed significantly between the two groups (7.9% versus 26.3%; p  = 0.000). According the clinical use of screening test criteria, LDA was prescribed in 63 (29.4%) women in the PE-group and 55 (26.3%) in the VP-group ( p  = 0.516). There were no differences in onset of preeclampsia [4 (1.9%) versus 6 (2.9%); p  = 0.540]. No early or severe preeclampsia occurred in the whole population.